2019
DOI: 10.3390/biom9120834
|View full text |Cite
|
Sign up to set email alerts
|

N-glycomic Profile in Combat Related Post-Traumatic Stress Disorder

Abstract: Post-traumatic stress disorder (PTSD) develops in a portion of individuals exposed to extreme trauma. Glycosylation is a post-translational modification that affects protein functions and is altered in various pathophysiological states and aging. There are still no validated biomarkers of PTSD. The aim of this study was to evaluate the N-glycomic profile in 543 male Caucasian individuals (299 veterans with PTSD and 244 control subjects). The study included discovery (N = 233) and replication (N = 310) cohort. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…The severity of PTSD was not associated with different plasma N-glycans, and IgG N-glycans were similar between groups. In this study, patients with PTSD did not show signs of accelerated physiological aging on the GlycoAge Test compared to controls [281].…”
Section: Trauma-and Stressor-related Disordersmentioning
confidence: 46%
See 1 more Smart Citation
“…The severity of PTSD was not associated with different plasma N-glycans, and IgG N-glycans were similar between groups. In this study, patients with PTSD did not show signs of accelerated physiological aging on the GlycoAge Test compared to controls [281].…”
Section: Trauma-and Stressor-related Disordersmentioning
confidence: 46%
“…In another study looking for PTSD biomarkers, N-glycomic profiles of 299 male veterans with PTSD were compared to 244 healthy controls [281]. Results showed that six plasma N-glycans were significantly altered in patients with PTSD compared to controls.…”
Section: Trauma-and Stressor-related Disordersmentioning
confidence: 99%
“…Post-traumatic stress disorder (PTSD) is a complex, trauma- and stressor-related disorder that develops in a subset of individuals as a result of direct or indirect exposure to a stressful or traumatic event(s) [ 1 , 2 ]. It is characterized by typical clusters of symptoms that include intrusive memories and re-experiencing, persistent avoidance, negative alterations in cognition and mood and changes in both physical and emotional reactions, including elevated arousal and reactivity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with previous findings by Moreno-Villanueva and colleagues [ 5 ], who reported N-glycosylation changes related to accelerated aging in the patients with PTSD in comparison to the control group. Moreover, a recent study showed significant alterations in several plasma N-glycan levels, mostly tri- and tetra-antennary, highly galactosylated and sialyated N-glycans, in the patients with PTSD compared to healthy control subjects [ 1 ]. Changes in the N-glycan profile have also been associated with schizophrenia [ 14 , 15 ] and major depressive disorder [ 16 ], suggesting that PTSD shares similar biological and molecular foundations with other neuropsychiatric disorders that are characterized by the acute or chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this Special Issue is a snapshot of a collective view of Biomolecules on biomolecules. The covered topics range from the description of secondary metabolites produced by fungi [ 1 ] to the overview of the phytochemical composition and pharmacological and food applications of Prosopis plants [ 2 ], to comparative evaluation of the antiproliferative activity of plant-derived silver nanoparticles synthesized using callus and anthocyanin extracts of purple basil (BC-AgNPs and AE-AgNPs, respectively) [ 3 ], to systematic description of the utilization of natural products as a source of antitumor drugs [ 4 ], to the analysis of the effects of caffeine and other methylxanthines on Aβ-homeostasis by shifting the α- and β-secretase-based processing of amyloid precursor protein (APP) from the Aβ-producing amyloidogenic to the non-amyloidogenic pathway [ 5 ], to the topoisomerase I and radical trapping antioxidant activities of a series of N-alkyl-acridones and N,N′-dialkyl-9,9′-biacridylidenes [ 6 ], to the analysis of the effects of phytoalexins in soybeans via synergistic inhibition on α-glucosidase [ 7 ], to functional and structural characterization of several important proteins (such as the analysis of the general and genomic DNA-binding specificity of a transcription factor TTHB023 from Thermus thermophilus HB8 [ 8 ], investigation of the voltage sensing in protein translocation via the bacterial channel SecYEG [ 9 ], and structural characterization of the terminase (packaging protein) pUL15, which is the most conserved among all the Herpes Simplex Virus 1 (HSV1) gene products [ 10 ]), to the description of utilization of kinetic transition in amyloid assembly for screening fluorophores for preferential responses to oligomer over fibril formation [ 11 ], to the description of the utilization of amyloid fibril biomaterials, designer amyloid cell-penetrating peptides comprised of β-sheet cores derived from naturally occurring protein sequences and designed positively charged and aromatic residues exposed at key residue positions as gene transfer vehicles capable of self-assembling and promoting the DNA condensation and cell internalization [ 12 ], to the introduction of the use of phage display system for generation of lamprey monoclonal antibodies, lampribodies, which are the variable lymphocyte receptors (VLRs) consisting of leucine rich repeats (LRRs), whose diversity is generated by stepwise genomic rearrangements of LRR cassettes dispersed throughout the VLRB locus [ 13 ], to the description of changes in the N-glycomic profile associated with post-traumatic stress disorder (PTSD) via comparative analysis of the N-glycomic profiles in 543 male Caucasian individuals (299 veterans with PTSD and 244 control subjects) [ 14 ], to the analysis of the effect of macromolecular crowding on the functionality of tumor suppressors ING containing a plant homeodomain (PHD) and their ability to interact with the histone H3 trimethylated at lysine 4 (H3K4me3) [ 15 ], and to the compariso...…”
mentioning
confidence: 99%